2011
DOI: 10.1186/1758-2652-14-3
|View full text |Cite
|
Sign up to set email alerts
|

Quality of data collection in a large HIV observational clinic database in sub‐Saharan Africa: implications for clinical research and audit of care

Abstract: BackgroundObservational HIV clinic databases are now widely used to answer key questions related to HIV care and treatment, but there has been no systematic evaluation of their quality of data. Our objective was to evaluate the completeness and accuracy of recording of key data HIV items in a large routine observational HIV clinic database.MethodsWe looked at the number and rate of opportunistic infections (OIs) per 100 person years at risk in the 24 months following antiretroviral therapy (ART) initiation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…Greatly improved access to ART [5], and knowledge of the efficacy of treatment to reduce transmission likely contributes to the high proportion (20–50%) of persons living with HIV (PLWHIV) who desire to have children in Uganda [68] and the larger region [9–12]. In fact, 20–40% of HIV-infected women become pregnant post-HIV diagnosis [13, 14], and nearly 100,000 HIV-infected women become pregnant annually in Uganda [15].…”
Section: Introductionmentioning
confidence: 99%
“…Greatly improved access to ART [5], and knowledge of the efficacy of treatment to reduce transmission likely contributes to the high proportion (20–50%) of persons living with HIV (PLWHIV) who desire to have children in Uganda [68] and the larger region [9–12]. In fact, 20–40% of HIV-infected women become pregnant post-HIV diagnosis [13, 14], and nearly 100,000 HIV-infected women become pregnant annually in Uganda [15].…”
Section: Introductionmentioning
confidence: 99%
“…The data quality is poor in about 5% of records in health organisations 2325. Many studies regularly report a range of deficiencies in the routinely collected electronic information for clinical6,26 or health promotion23 purposes in hospital27 and general practice28 settings.…”
Section: Discussionmentioning
confidence: 99%
“…A majority of clinics providing HIV care and treatment in SSA use a fixed list of coarse-grained ADIs to perform clinical staging of HIV-infection as recommended by WHO [8]. Kiragga et al estimate that ADIs in clinical settings are under-reported by up to 67% in HIV clinics in Uganda [10]. Classification and terminology systems are increasingly used in developed countries for clinical documentation [12].…”
Section: Introductionmentioning
confidence: 99%
“…Classification and terminology systems are increasingly used in developed countries for clinical documentation [12]. Lack of a structured, uniquely coded and comprehensive set of ADIs based on a terminology standard, from which diagnoses can be documented to support clinical decisions such as eligibility for antiretroviral therapy can potentially compromise the quality of care [10,13]. Additionally, in busy clinics with over-worked health workers, ADIs are rarely recorded with a fine granularity including more specific disease sub-types.…”
Section: Introductionmentioning
confidence: 99%